Critical Discourse Analysis in Donald Trump Presidential Campaign to Win American's Heart - Andhita Rachman; Sofi Yunianti; Dwijani Ratnadewi (Tell : Teaching of English Language and Literature Journal, 2017)
Politic is always related to activities that influence the action and policies in government or society. This activity will gain or keep power on it. This research aimed to analyze Donald Trump’s utterances in his presidential campaign at November 16th, 2015 in Knoxville Convention Center. There are four objective of the research that must be answered; 1) The utterances that illustrated political discourse in Donald Trump Speech; 2) The way he delivered his political discourse; 3) The aim of the utterances; 4) Effect of the utterance to people. Descriptive qualitative was applied as the method of the research and the data of the research were the utterances that illustrated Donald Trump’s political discourse. The utterances were being analyzed using CDA’s Van Dijk supported by Fairclough and Wodak theory. The result showed his way to deliver his ideology in gaining power where in power; there is an ability to control people which in line with his purpose to win American’s heart. Trump’s political strategies succeeded to gain many supports that made him elected as the presidential candidate from the Republic party.